102. Surgical Treatment of Brachial Artery Aneurysm Associated qith Arteriovenous Shunt for Hemodialysis: Case Report - Sanjaya, Carolus Eko; Sudiasa, Ketut (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Introduction : A brachial artery aneurysm is a rare complication of an arteriovenous fistula (AVF) created for hemodialysis access. This report details the case of a patient with a brachial artery aneurysm associated with an AVF for hemodialysis, who underwent successful surgical treatment.   Case : A 64-year-old female with CKD undergoing regular hemodialysis presented with a painful lump in her right arm one-week AVF installation. Her medical history included a left nephrectomy in 2022, previous failed AV fistula placement, and central dialysis line (CDL) insertion. The patient had a medical history significant for CKD requiring routine HD twice a week. Local examination of the patient's right arm revealed a mobile, painful lump, diagnosed as a brachial artery aneurysm, limiting arm movement. A chest X-ray showed cardiomegaly, thoracic spondylosis, and proper CDL positioning. Laboratory results were normal. The patient underwent surgical repair of the aneurysm and was hospitalized for three days postoperatively. Post-surgery treatment included analgesics, antibiotics, anticoagulation therapy, and outpatient clopidogrel. Conclusions : A brachial artery aneurysm is a rare complication of an AVF, posing risks of peripheral embolism and hand ischemia, and therefore requires surgical correction.